Ternary solution-processed organic solar cells incorporating 2D materials. (8th September 2017) - Stylianakis, Minas M; Konios, Dimitrios; Petridis, Constantinos; Kakavelakis, George; Stratakis, Emmanuel; Kymakis, Emmanuel
Abstract: Recently, the study of ternary organic solar cells (OSCs) has attracted the efforts of the scientific community, leading to significantly higher performance due to the enhanced harvesting of incoming irradiation. Here, for the first time, and in order to promote this OSC architecture, we review the progress implemented by the application of two-dimensional (2D) materials in the field of blend bulk heterojunction ternary OSCs. Power conversion efficiency (PCE) improvements of the order of 40% compared to the reference binary devices, and PCEs in excess of 8% have been reported by incorporating graphene-based or other 2D materials as a third element inside the active layer. These OSCs combine the synergetic advantages of ternary devices and the superb properties of the 2D material family. In conclusion, the incorporation of the unique properties of graphene and other 2D materials inside the active layer opens up a very promising pathway in the design and construction of high-performance, simply fabricated and low- cost photovoltaic devices.